Yakuza : - Kaplan, David E. (Addison-Wesley, 1986)
Yakuza introduces the story of orga nized crime in Japan : its history (con centrating on the post-World War II period); its organization, culture, and principal figures; and its activities in Japan and other countries, especially the United States. The account is based upon a wide variety of sources, including interviews and government reports, but the heavy reliance upon newspaper stories contributes to an often sensationalistic style. This is not the definitive study, but it does a rea sonable job of addressing an important and neglected topicthere is very lit tle book-length material in English about the yakuza. Appropriate for both general and subject collections. Kenneth W. Ber ger, Duke Univ. Lib., Durham, N.C.